The Great COVID-19 Divergence: Managing a Sustainable and Equitable Recovery in the EU - Grégory Claeys; Zsolt Darvas; Maria Demertzis; Guntram B. Wolff (Intereconomics, 2021)
The COVID-19 pandemic has led to the biggest global recession since the Second World War. Forecasts show the European Union underperforming economically relative to the United States and China during 2019–2023. Southern European countries have been particularly strongly affected. Some sectors have been hit harder than others. Business insolvencies have, paradoxically, fallen. While total employment has almost recovered, the young and those with low-level qualifications have suffered employment losses. Inequality could rise. The pandemic may lead to lasting changes in the economy, with more teleworking, possibly higher productivity growth and changed consumer behaviour. Policymakers must act to prevent lasting divergence within the EU and scarring due to the fallout from the pandemic. The first priority is tackling the global health emergency. Second, the article warns against premature fiscal tightening but suggests additional short-term support to prevent scarring. Third, the article warns against protectionism and advocates for reforms that boost productivity growth further.
Keywords: 330; Coronavirus; Epidemie; Wirtschaftslage; Wirtschaftspolitik; EU-Staaten